Online education model on coffee addiction on the prevention of diabetes mellitus - Halimatussakdiah Halimatussakdiah; T. Iskandar Faisal (AcTion: Aceh Nutrition Journal, 2022)
Diabetes Mellitus (DM) starts with unhealthy changes in life behavior. Unhealthy patterns and lifestyles are considered fun without regard to the negative impacts that can last a long time. This study aimed to identify the influence of online education factors on coffee addicts on DM prevention. Quantitative research using a quasi-experimental design. The sample was 450 people. The research was conducted in 6 districts, namely Aceh Besar, Banda Aceh, West Aceh, South Aceh, Lhokseumawe and East Aceh, from August 1, 2021, to October 30, 2021. The sampling technique used was the Multistage sampling method—sample calculation using SEM standards. The independent variables are online education and Shari'a video, while the dependent variable is DM prevention. Data collection using a questionnaire in the form of a Likert scale (1-5). Demographic data analysis used SPSS, while data analysis to test the influence between variables using Structural Equation Modeling (SEM). The results showed that online education through Shari'a videos could improve DM prevention. The variables tested in the development of the model, namely, online education and syar'i videos, affect DM prevention. The SEM test results obtained the GFI (Goodness of Fit Index) value at an alpha value ≤ 0,05. In conclusion, online education can be used as a medium to educate coffee addicts because it supports DM prevention.